Social representations and culture in food studies. (January 2019) - Lo Monaco, Grégory; Bonetto, Eric
Abstract: An important amount of studies investigates food, individuals and groups' relation to food. Some of them convoke the theoretical framework of social representations. These ones refer to structured sets of ideas, opinions, knowledge and beliefs about food shared by a social group, about food, foodstuffs, or related issues. The present contribution highlights the relevance of investigating the interaction between social representations and culture in such works following three main lines, corresponding to three ways to envisage the contribution of SRs to food studies. The first one focuses on the role of SRs in the social construction of meanings attached to food and on their introduction in individuals' and groups' thinking frameworks. This line present the shaping role of culture for representations. The second one is interested in how the sharing of SRs allows identification to the cultural group. This line highlights a lack of experiments and some research perspectives. The third one envisages social representations as predictors of consumers' behaviors. In this line, culture represents an important factor, especially through the individualist versus collectivist cultures. The results and the considerations from these three lines militate in favor of the consideration of culture and cultural variables in food studies using the theoretical framework of SRs. Certainly, the relevance of such a consideration is motivated by the intrinsic theoretical link between SRs and culture, but also shows a great interest when we want to gain a finer grained vision of the phenomenon under study in food research. Highlights: There is a lack of experiments concerning the sharing of social representations which allows identification to the cultural group. Social representations can be considered as predictors of consumers' behaviors.